Correction to: Importance of livestock diseases identified using participatory epidemiology in the highlands of Ethiopia - Gizaw, Solomon; Desta, Hiwot; Alemu, Biruk G.; Tegegne, Azage; Wieland, Barbara (Springer, 2021)
An erratum to this paper has been published: 10.1007/s11250-021-02593-7